Development of a robot OLP system for the continuous motion control of a mandrel in the radial braiding process - Han, Jeongho; Lee, Jinwon; Yang, Jeongsam (Journal of Mechanical Science and Technology, 2022)
The quality of a braid preform generated by the braiding process is affected by the movement path and speed. Previous studies have obtained an optimal movement path and an efficient speed profile of the mandrel, but no studies have considered robot kinematics for the mandrel’s motion, thereby causing errors occur during the braiding process. This study developed an off-line programming system that generates an optimal mandrel movement path to produce a high-quality preform based on the 3D curvature shape of the mandrel. This movement path is then converted into a robot command. The via-points for the robot path generation were extracted from the mandrel surface geometry. Afterwards, the process of generating a continuous motion and rearranging the via-points for radial braiding was performed. Continuous motion was created by separating the straight and curved paths, and the via-point rearrangement was applied depending on the change in speed.
Keywords: Continous motion; Mandrel control; Off line programming; Off-line programming; Optimal movements; Programming system; Radial braiding process; Robot kinematics; Speed profile; Via point; Mandrel control; Off-line programming (OLP); Path planning; Radial braiding process